From Inception to Implementation: Strategies for Setting Up Pulmonary Telerehabilitation - Santos, Catarina Duarte; Rodrigues, Fátima; Caneiras, Cátia; Bárbara, Cristina (Frontiers in Rehabilitation Sciences, 2022)
Background: The emergence of innovative technology-enabled models of care is an opportunity to support more efficient ways of organizing and delivering healthcare services and improve patient experience. Pulmonary telerehabilitation started as a promising area of research and became a strategic pandemic response to patients decreased accessibility to rehabilitation care. Still in the pre-COVID-19 era, we conducted a participatory research aiming to develop strategies for setting up pulmonary telerehabilitation as a digitally-enabled, integrated person-centred model of care. Methods: Operational participatory research between June of 2019 to March of 2020 with the engagement of all stakeholders involved on the implementation of pulmonary telerehabilitation, including 14 people with Chronic Obstructive Pulmonary Disease. Patients were assessed subjectively and objectively pre and post a 3-month pulmonary rehabilitation program including exercise and education, which started face-to-face at hospital setting during the first month and continued to a home-based remotely supervised exercise training intervention. Results: Five major group of requirements targeted operational strategies for setting up pulmonary telerehabilitation: 1) pulmonary rehabilitation core principles, 2) quality and security standards, 3) technological functionality, 4) home environment appropriateness and 5) telesetting skills. Patients reported improvement in quality of life with a decrease in CAT score of -5.9 ± 5.8 (p = 0.002) and in self-efficacy with an increase in PRAISE score of 3.6 ± 3.7 (p = 0.003). Patients’ mean level of satisfaction about rehabilitation goals achievement was of 88.1% ± 8.6% and mean level of satisfaction about telerehabilitation experienced as a model of care was of 95.4% ± 6.3%. Conclusions: The success of telerehabilitation implementation was grounded on stakeholders’ engagement and targeted strategies for specific setting up requirements, with patients’ high satisfaction level. Such operational experience should be integrated on redesigning upgraded telerehabilitation programs, as part of the solution to improve the effectiveness, accessibility, and resilience of health systems worldwide.